(untitled) (Journal of Oriental Studies, 2017)
The scientific article is devoted to the problems and peculiarities of translation of literary texts, especially literary texts from Korean into the Kazakh language, as the literary texts are a major part of every nation and culture. The importance of identifying features of the Kazakh and other languages, training of future specialists, strengthening socio-cultural relations between the Republic of Kazakhstan and other countries specified in the laws of language policy. The relevance of this article lies in the fact that these provisions require a thorough research in the field of translation from the Kazakh language into other languages, and additional new facts and conclusions.